Pengaruh Pendidikan Dan Pelatihan Kompetensi Dan Motivasi Terhadap Kinerja Tenaga Penyuluh Keluarga Berencana Di Kabupaten Aceh Besar - Sri Raihan; Titi Darni; Hedi Heryadi (CV The Journal Publishing, 2022)
Abstract: The performance of Family Planning Extension Workers (PKB) has not been able to provide maximum service to family planning participants in Aceh District to obtain information and various services related to family planning, especially in Aceh Besar District.The purpose of this research isanalyze the influence of education and competency training and work motivation simultaneously or partially on the performance quality of Family Planning Extension Workers in Aceh Besar District.The population in the study were 61 people. In this study the entire population was sampled.The research results show thatjointly prove that competency education and training and work motivation jointly have an influence on improving the quality of PKB performance in Aceh Besar District, this is evidenced by the Fcount value of 50.242 and Ftable of 3.155 thus Fcount > Ftable, so the alternative hypothesis (Ha) which was proposed to get the results accepted and rejected the null hypothesis (Ho). While the partial results of the research on competency education and training have had an impact on improving the quality of PKB performance in Aceh Besar District, in this case the tcount is 3.679, so that the hypothesis (Ha) that has been proposed is accepted and rejects the null hypothesis (Ho). Then for the work motivation variable it also has an impact on improving the quality of PKB performance in Aceh Besar District.